2020
DOI: 10.3390/cancers12123621
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 Regulation by Noncoding RNAs in Cancers: The Present Knowledge and the Way Forward

Abstract: Nuclear factor erythroid 2-related factor 2 (NRF2) is the key transcription factor triggered by oxidative stress that moves in cells of the antioxidant response element (ARE)-antioxidant gene network against reactive oxygen species (ROS) cellular damage. In tumors, the NRF2 pathway represents one of the most intriguing pathways that promotes chemo- and radioresistance of neoplastic cells and its activity is regulated by genetic and epigenetic mechanisms; some of these being poorly investigated in cancer. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 117 publications
(130 reference statements)
0
16
0
Order By: Relevance
“…A wealth of studies has illustrated the irreplaceable role of lncRNAs in the interplay of transcription controls in gene expression (Gowthaman et al, 2020;Guo et al, 2020b). LncRNAs are crucial regulators in diverse cellular contexts and biological processes, especially in cancers where they are linked to carcinogenesis and tumor progression both at transcriptional and posttranscriptional levels (Fabrizio et al, 2020). TMPO-AS1, a newly identified lncRNA, plays an essential role in carcinogenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of studies has illustrated the irreplaceable role of lncRNAs in the interplay of transcription controls in gene expression (Gowthaman et al, 2020;Guo et al, 2020b). LncRNAs are crucial regulators in diverse cellular contexts and biological processes, especially in cancers where they are linked to carcinogenesis and tumor progression both at transcriptional and posttranscriptional levels (Fabrizio et al, 2020). TMPO-AS1, a newly identified lncRNA, plays an essential role in carcinogenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ncRNAs including miRNAs, lncRNAs and circRNAs are involved in regulating gene expression through the mechanism of ceRNA [25][26][27][28][29] . To explore upstream regulatory miRNAs of GNG5, we introduced two predictive programs, including miRmap and TargetScan, to predict miRNAs that may bind to GNG5.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ncRNAs including miRNAs, lncRNAs and circRNAs are involved in regulating gene expression through the mechanism of ceRNA [30][31][32][33][34] . To explore upstream regulatory miRNAs of GNG5, we introduced two predictive programs, including miRmap and TargetScan, to predict miRNAs that may bind to GNG5.…”
Section: Discussionmentioning
confidence: 99%